A monocyclic neodysiherbaine analog: Synthesis and evaluation. Issue 21 (1st November 2016) - Fukushima, Koichi; Ishikawa, Yuichi; Sakai, Ryuichi; Oikawa, Masato
Graphical abstract: Abstract: Monocyclic analog of neuroexcitatory neodysiherbaine has been designed and stereoselectively synthesized in 0.40% yield over total 24 steps starting fromd -ribose, by employing domino aldol-Cannizzaro reaction and stereoselective aldol reaction for construction of two quaternary carbon stereogenic centers at C4 and C6 positions, respectively. The hyperactivity of neodysiherbaine in mice was found to deteriorate in the novel analog, upon intracerebroventricular injection.